Customer Relationship Management (CRM) Strategies In Small And Medium Enterprises (SMES): A Study In Tourism Industry In Vietnam - Ngo, Vu Minh; Vu, Hieu Minh; Nguyen, Mai Hong (International Journal of Psychosocial Rehabilitation, 2020)
Small and Medium Enterprises (SMEs) are one of the main motors for economic growth, especially in developing countries like Vietnam. However, SMEs are usually overlooked in academic research on the topic of firms ‘competitive advantage. Taking the fact that Customer Relationship Management (CRM) has currently been one of the most popular tools in the business for building long term competitive advantage. The main objectives of this study are to investigate which CRM strategies are currently being implemented in SMEs and identify factors that determine the success of CRM implementation in SMEs. Using the adoption of grounded theory research procedures, this study investigates the practices of CRM implementation in 41 SMEs in the tourism industry in Vietnam. This study provides more insights and guidelines for managers in SMEs so that they can